Reusing and Recycling of Secondary Batteries - Paz-García, Juan Manuel; Villén-Guzmán, María Dolores; Cerrillo-González, María del Mar (My University, 2019)
Reusing and Recycling of Secondary Batteries
Invited oral presentation
Keywords: Baterías secundarias; Battery recycling